ダイ 24 ジ エットウ タイ カイヨウ セイブツ (BIOMASS ケイカク 2 ネンジ) カンソク ホウコク 1983/84 - 渡辺, 研太郎; ワタナベ, ケンタロウ; 佐藤, 博雄; サトウ, ヒロオ; 神田, 啓史; カンダ, ヒロシ; 高橋, 永治; タカハシ, エイジ; Watanabe, Kentaro; Satoh, Hiroo; Kanda, Hiroshi; Takahashi, Eiji (1986)
P(論文) 第24次南極地域観測隊は, 海洋生物を中心とした3年間におよぶ連続観測計画の第2年次を担当し, 1983年2月から1984年1月の間, 昭和基地周辺定着氷上で調査・観測を行った。第2年次の主な調査対象は, 海氷下の植物プランクトン, アイスアルジー, 原生生物などの基礎生産者で, 現存量・種組成・一次生産に関する調査を実施した。このほか海洋細菌, アデリーペンギンの個体数などの調査を行った。5月初めに昭和基地周辺の海氷が流失し, 調査が一時中断したが, 前次隊からの観測を継続することにより, 植物プランクトンの現存量が1月中旬から2月中旬に最大となることなどが明らかになった。調査結果は今後別個に発表されるので, ここでは概要にふれるにとどめ, 第24次観測隊の準備状況および調査・観測の実施状況について報告する。 The 24th Japanese Antarctic Research Expedition (JARE-24) took charge of the second year survey of the three-year programme for Antarctic marine biological investigations near Syowa Station. The second year programme was planned to lay stree on primary producers in water column and in sea ice. Investigations on seasonal variations of standing stock, species composition and primary productivity of phytoplankton and ice-associated microalgae were carried out from February 1983 to January 1984. In addition, marine bacterial study and population census of the Adelie penguin were performed. Successive observations from the former party (JARE-23) revealed that the standing stock of phytoplankton reached the maximum between middle January and middle February in 1983,although the present research was interrupted in early May by the outflow of fast ice around Syowa Station. Details of technical and logistic aspects on field works are given in this report. Information on the planning and preparation in Japan is also mentioned where necessary. departmental bulletin paper